2021
DOI: 10.1186/s12879-021-06450-8
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for mortality in patients over 70 years old with COVID-19 in Wuhan at the early break: retrospective case series

Abstract: Background Elderly patients with COVID-19 were shown to have a high case-fatality rate. We aimed to explore the risk factors associated with death in patients over 70 years old (yr). Methods In this retrospective study, we enrolled consecutively hospitalized patients over 70 yr with COVID-19 between January 20 and February 15, 2020 in Renmin Hospital of Wuhan University. Epidemiological, demographic, and clinical data were collected. Clinical subty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 25 publications
(30 reference statements)
1
11
0
Order By: Relevance
“…Strong evidence has been accumulated since the beginning of the COVID-19 pandemic that neutrophils play an important role in the pathogenesis of severe disease course and that neutrophilia represents a feasible and inexpensive biomarker of COVID-19 severity ( Wu et al, 2020 ). In COVID-19 patients, neutrophilia associated with lymphopenia was observed in patients with increased disease severity and with poor prognosis ( Picchi et al, 2021 , Yang et al, 2020 , Zhu et al, 2021 ). A number of studies showed a correlation between markers derived from standard blood count tests, such as neutrophil-to-lymphocyte ratio (NLR), derived NLR ratio (dNLR, neutrophil count divided by the result of WBC count minus neutrophil count), platelet-to-lymphocyte ratio (PLR), and lymphocyte-to-monocyte ratio (LMR) and systematic inflammatory response in a number of age-related diseases, including cancer ( Xu et al, 2021 , Ying et al, 2014 ), type 2 diabetes mellitus (T2DM) ( Tong et al, 2004 ), cardiovascular diseases (CVD) ( Bhat et al, 2013 , Ji et al, 2021 ), and stroke ( Cai et al, 2021a ).…”
Section: Discussionmentioning
confidence: 99%
“…Strong evidence has been accumulated since the beginning of the COVID-19 pandemic that neutrophils play an important role in the pathogenesis of severe disease course and that neutrophilia represents a feasible and inexpensive biomarker of COVID-19 severity ( Wu et al, 2020 ). In COVID-19 patients, neutrophilia associated with lymphopenia was observed in patients with increased disease severity and with poor prognosis ( Picchi et al, 2021 , Yang et al, 2020 , Zhu et al, 2021 ). A number of studies showed a correlation between markers derived from standard blood count tests, such as neutrophil-to-lymphocyte ratio (NLR), derived NLR ratio (dNLR, neutrophil count divided by the result of WBC count minus neutrophil count), platelet-to-lymphocyte ratio (PLR), and lymphocyte-to-monocyte ratio (LMR) and systematic inflammatory response in a number of age-related diseases, including cancer ( Xu et al, 2021 , Ying et al, 2014 ), type 2 diabetes mellitus (T2DM) ( Tong et al, 2004 ), cardiovascular diseases (CVD) ( Bhat et al, 2013 , Ji et al, 2021 ), and stroke ( Cai et al, 2021a ).…”
Section: Discussionmentioning
confidence: 99%
“…The risk of hospitalization in 74–65 years is five times more than in the age group of 18–29 years. 9 , 10 …”
Section: Introductionmentioning
confidence: 99%
“…Likewise, the rate of COVID‐19 hospitalization increases with advanced age. The risk of hospitalization in 74–65 years is five times more than in the age group of 18–29 years 9,10 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…COVID-19, caused by the Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2), was first declared a global emergency by the WHO in January 2020,1 with the UK documenting its first case in February 2020 2. SARS-CoV-2 is more transmissible compared with other viral acute respiratory syndromes (ARS),3 with mortality particularly high in those aged 70 years and older 4. Additionally, an increased proportion of COVID-19 symptomatic patients require hospital admission for supportive respiratory management compared with previous ARS pandemics 5.…”
Section: Introductionmentioning
confidence: 99%